The migration of synthetic magnetic nanoparticle labeled dendritic cells into lymph nodes with optical imaging - Su H; Mou YB; An YL; Han W; Huang XF; Xia GH; Ni YH; Zhang Y; Ma JM; Hu QG (International Journal of Nanomedicine, 2013)
Hang Su,1,* Yongbin Mou,1,* Yanli An,2 Wei Han,1 Xiaofeng Huang,1 Guohua Xia,3 Yanhong Ni,1 Yu Zhang,4 Jianmin Ma,1 Qingang Hu1,5 1Center Laboratory of Stomatology, Stomatological Hospital Affiliated Medical School, Nanjing University, Nanjing, People's Republic of China; 2Jiangsu Key Lab of Molecular and Function Imaging, Department of Radiology; 3Department of Hematology, Zhongda Hospital, Medical School, 4State Key Laboratory of Molecule and Bimolecular Electronics, Jiangsu Provincial Laboratory for Biomaterials and Devices; Southeast University, Nanjing, People's Republic of China; 5Leeds Dental Institute, Faculty of Medicine and health, University of Leeds, Leeds, United Kingdom*These authors contributed equally to this workBackground: The successful biotherapy of carcinoma with dendritic cell (DC) vaccines pivotally relies on DCs’ migratory capability into lymph tissues and activation of T cells. Accurate imaging and evaluation of DC migration in vivo have great significance during antitumor treatment with DC vaccine. We herein examined the behavior of DCs influenced by synthetic superparamagnetic iron oxide (SPIO) nanoparticle labeling.Methods: γ-Fe2O3 nanoparticles were prepared and DCs, which were induced from bone marrow monocytes of enhanced green fluorescent protein (EGFP) transgenic mice, were labeled. The endocytosis of the SPIO, surface molecules, cell apoptosis and fluorescence intensity of EGFP-DCs were displayed by Prussian blue staining and flow cytometry (FCM), respectively. After EGFP-DCs, labeled with SPIO, were injected into footpads (n = 5) for 24 hours, the mice were examined in vivo by optical imaging (OPI). Meanwhile, confocal imaging and FCM were applied, respectively, to detect the migration of labeled DCs into draining lymph nodes.Results: Nearly 100% of cells were labeled by the SPIO, in which the intracellular blue color gradually deepened and the iron contents rose with the increase of labeling iron concentrations. In addition, cell apoptosis and the surface molecules on DCs were at similar levels after SPIO labeling. After confirming that the fluorescence intensity of EGFP on DCs was not influenced by SPIO, the homing ability of EGFP-DCs labeled with SPIO displayed that the fluorescence intensity and the ratios of EGFP-DCs in draining lymph nodes were gradually decreased with the increase of labeling iron concentrations.Conclusion: The synthetic SPIO nanoparticles possess perfect labeling ability and biocompatibility. Moreover, DCs labeled with a low dose of SPIO showed stronger migratory capability in vivo.Keywords: optical imaging, dendritic cell, superparamagnetic iron oxide, cell tracking